Forced Migration: The Case of Armenia – 1915 and beyond - Gasparyan, Seda (Armenian Folia Anglistika, 2015)
The article aims to discuss the question of deportations as part of the genocidal process, accomplished in western Armenia by the Turks particularly in 1915. Allegations intentionally pushed forward by the Turkish rulers of the period claiming that Armenians were treacherous separatists served as a “well-grounded” justification for them to administer the wholesale deportation of the Armenian population first from eastern and south-eastern provinces, then the capital city Constantinople and other major cities of the empire. The investigation of documented facts as well as the results of other researches shows that the idea of the deportations was conceived and promulgated in 1915 to mask the pre-planned genocidal actions which had come into full swing long before. The Ottoman authorities were somewhat taken aback after they received the joint declaration issued by Great Britain, Russia and France laying the responsibility of the horrendous actions against humanity and civilization taking place in Turkey to the charge of the members of the Ottoman government. They hoped the Deportation Law could rid them of responsibility.